Árbol de códigos del estudio cualitativo sobre psicosis y esquizofrenia - Hurtado Lara, Mª Magdalena; Morales-Asencio, José Miguel (My University, 2021)
Below is the code tree of a qualitative study conducted with the participation of people diagnosed with psychosis and schizophrenia. Focus groups and in-depth interviews were conducted to explore how these people coped with their disorder and their opinion about the healthcare they were receiving, and this file shows the codes obtained and the number of times they referred.
Keywords: Psicosis; Esquizofrenia; Investigación cualitativa; Psychoses; Schizophrenia; Qualitative research